Evaluation of Pulmonary and Systemic Toxicity of Oil Dispersant (COREXIT EC9500A®) following Acute Repeated Inhalation Exposure. (January 2014) - Roberts, Jenny R.; Anderson, Stacey E.; Kan, Hong; Krajnak, Kristine; Thompson, Janet A.; Kenyon, Allison; Goldsmith, William T.; McKinney, Walter; Frazer, David G.; Jackson, Mark; Fedan, Jeffrey S.
Introduction: Oil spill cleanup workers come into contact with numerous potentially hazardous chemicals derived from the oil spills, as well as chemicals applied for mitigation of the spill, including oil dispersants. In response to the Deepwater Horizon Macondo well oil spill in the Gulf of Mexico in 2010, a record volume of the oil dispersant, COREXIT EC9500A, was delivered via aerial applications, raising concern regarding potential health effects that may result from pulmonary exposure to the dispersant. Methods: The current study examined the effects on pulmonary functions, cardiovascular functions, and systemic immune responses in rats to acute repeated inhalation exposure of COREXIT EC9500A at 25 mg/m 3, five hours per day, over nine work days, or filtered air (control). At one and seven days following the last exposure, a battery of parameters was measured to evaluate lung function, injury, and inflammation; cardiovascular function; peripheral vascular responses; and systemic immune responses. Results: No significant alterations in airway reactivity were observed at one or seven days after exposure either in baseline values or following metha-choline (MCh) inhalation challenge. Although there was a trend for an increase in lung neutrophils and phagocyte oxidant production at one-day post exposure, there were no significant differences in parameters of lung inflammation. In addition, increased blood monocytes and neutrophils, and decreased lymphocyte numbers at one-day post exposure also did not differ significantly from air controls, and no alterations in splenocyte populations, or serum or spleen immunoglobulin M (IgM) to antigen were observed. There were no significant differences in peripheral vascular responsiveness to vasoconstrictor and vasodilator agonists or in blood pressure (BP) responses to these agents; however, the baseline heart rate (HR) and HR responses to isoproterenol (ISO) were significantly elevated at one-day post exposure, with resolution by day 7. Conclusions: In summary, acute repeated exposure to COREXIT EC9500A did not alter pulmonary function, lung injury/inflammation, systemic immune responses, or vascular tone, but did cause transient chronotropic effects on cardiac function.